Technology Blueprint: Smart Dusbin / Mohammad Muaz Nordin - Nordin, Mohammad Muaz (2020)
My company offers a product called Smart Dustbin to store our customer’s garbage before it being dump into a landfill. Smart Dustbin is an automatic dustbin comes with and LED light. Our product is user-friendly and easy to use as it is an automatic product. We also offer affordable price with a good quality product. Our product and design will continue to develop based on consumer trends and demands Smart Dustbin is targeted to local family, students and office workers and the products is focused to be marketed towards buyers with low income. The reason is because the product uses reliable yet cheap materials to be produced. Product would be placed at hardware shop and online website for wider reach